The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1967
DOI: 10.1111/j.1445-2197.1967.tb06989.x
|View full text |Cite
|
Sign up to set email alerts
|

Pilonidal Sinus Treated by Z‐Plasty1

Abstract: The rationale and technique of Z‐plasty treatment for sacro‐coccygeal pilonidal sinus are presented. Z‐plasty achieves healing by primary intention, and by modification of the local environment prevents recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1968
1968
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Most of the infections and recurrences occur because of this difference in levels and because of the sutures left in these crossing areas and the deep midline gap created by all of the primary or partial closure procedures according to our observations and the literature. 7,14,17 In the invited commentary to the editor written by Bascom about the article by Akinci et al, 14 it was reported that such procedures were a major source of iatrogenic pilonidal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the infections and recurrences occur because of this difference in levels and because of the sutures left in these crossing areas and the deep midline gap created by all of the primary or partial closure procedures according to our observations and the literature. 7,14,17 In the invited commentary to the editor written by Bascom about the article by Akinci et al, 14 it was reported that such procedures were a major source of iatrogenic pilonidal disease.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological basis for this has been examined by McDermott [26] who found elimi nation o f negative subcutaneous pressure after Z-plasty. The recurrence rate after more extensive surgery varies from zero to 10% [21,22,25,26]. A skin flap procedure requires a long hospital stay and is not free from compli cations [21,22,25].…”
Section: Discussionmentioning
confidence: 99%
“…Oblique or asymmetric closure techniques, such as Karydakis flap 4,8 and the Bascom procedure, are based on this principle. 6,9 Similarly, full-thickness flap techniques, such as Z-plasty, Wplasty, V-Y fasciocutaneous flap, rhomboid flaps (Dufourmentel or Limberg flaps), and gluteus maximus rotational flap, are designed to flatten the natal cleft to prevent recurrences. Lower rates of pain, infection and recurrence, and more rapid wound healing after reconstruction of defects with flaps have been recently reported.…”
mentioning
confidence: 99%